Cognitive Correlation Between Sciences: Linguistics Example (Linguist, 2021)
Modern linguistics has made a great development towards integrating into the cognitive paradigm of science, which has allowed qualitative progress in understanding the network of causal relationships between the natural cognitive faculties of the human mind, including its physical, conceptual and cognitive faculties, such as social, linguistic, mindreading and other faculties. This is thanks to the findings of various cognitive sciences studying these faculties, whether they are natural and physical or psychological, social and behavioral sciences, such as neurosciences, computer sciences, physics, psychological and social sciences, cellular and molecular biology, genetics, bio-anthropology, primatology, etc.These findings revealed a complementarity between the topics of these sciences due to the intrinsic causal interdependence that exists between the various studied phenomena. This makes it possible to defend a “new naturalistic” stance on various sciences, “unifying” them on a relational, non-reductive, basis. We follow two steps in accounting for this:Determining what is meant by “unifying” sciences in the context of a new naturalistic stance; and highlighting some features of the cognitive paradigm based on the aforementioned causal interdependence between universal phenomena that shaped human being; and some cognitive outcomes of this paradigm, its sources and major goals.Identifying some aspects of the integration of modern cognitive linguistics in this paradigm, by providing examples of the interaction across interfaces between components of the linguistic system and the rest of perceptual and conceptual systems that constitute the overall structure of the mind/brain and are studied by various sciences mentioned above. These aspects are integrative manifestations that reflect, firstly, a deeper understanding of components of natural languages, their conceptual properties, analytical resources and neural origins; secondly, growing interest in elaboration of interface-constrained conceptions of language design, acquisition and use; thirdly, searching for characteristics in which language differs from, or has in common with, other faculties.
Keywords: cognitive paradigm; new naturalism; causal correlation; cognitive linguistics; interfaces; linguistic system; perceptual and conceptual systems